Propagation characteristics of Doppler ultrasonic wave in gas–liquid two-phase flow in an offshore deepwater riser - Chunwei Gu; Qian Li; Rui Ma; Yingsong Lin; Xiangfang Li; Yiming Li; Aixia Zhang; Yingjie Li; Bangtang Yin (Natural Gas Industry B, 2021)
During offshore deepwater drilling, the strata with abnormal pressure are often encountered and gas invasion and overflow occur easily. If they cannot be detected and controlled in time, blowout may happen and even get out of control, which will cause considerable economic loss and irreparable casualties and may even damage the marine ecologic environment seriously. How to monitor overflow early during deepwater drilling is a global research hot, focus and difficulty at present. In order to provide theoretical guidance for the early monitoring of overflow in the riser during offshore deepwater drilling, this paper designed an experimental device for the early monitoring of gas invasion based on the propagation principle of Doppler ultrasonic wave. Then, the installation mode and angle of Doppler probe were optimized. Finally, the propagation of Doppler ultrasonic wave in the gas–liquid two-phase flow with a void fraction of 0–46% and a liquid flow velocity of 0–0.7 m/s was experimentally studied, and the change laws of Doppler ultrasonic wave with void fraction were revealed. And the following research results are obtained. First, when the void fraction changes, the signal voltage will jump up and down at different amplitudes and frequencies on the basis of initial curve. The signal voltage amplitude increases firstly and then decreases with the increase of void fraction. Second, when the increase amplitude of mean signal voltage caused by multiple reflection is greater than the attenuation degree of ultrasonic wave, the mean signal voltage increases. Otherwise, the signal voltage decreases. Third, the fitting curve of mean signal voltage scatters and void fraction under different flow velocities and void fractions during pump stopping and starting present a change law of quadratic function. In conclusion, void fraction can be quantitatively predicted based on the measured signal voltage, so as to provide guidance for the early monitoring of riser overflow and well kill operation during offshore deepwater drilling.